Production of ginsenoside aglycone (protopanaxatriol) and male sterility of transgenic tobacco co-overexpressing three Panax ginseng genes: PgDDS, CYP716A47, and CYP716A53v2 - Yu Shin Gwak; Jung Yeon Han; Yong Eui Choi (Journal of Ginseng Research, 2019)
Background: Protopanaxatriol (PPT) is an aglycone of ginsenosides, which has high medicinal values. Production of PPT from natural ginseng plants requires artificial deglycosylation procedures of ginsenosides via enzymatic or physicochemical treatments. Metabolic engineering could be an efficient technology for production of ginsenoside sapogenin. For PPT biosynthesis in Panax ginseng, damarenediol-II synthase (PgDDS) and two cytochrome P450 enzymes (CYP716A47 and CYP716A53v2) are essentially required. Methods: Transgenic tobacco co-overexpressing P. ginseng PgDDS, CYP716A47, and CYP716A53v2 was constructed via Agrobacterium-mediated transformation. Results: Expression of the three introduced genes in transgenic tobacco lines was confirmed by Reverse transcription-polymerase chain reaction (RT-PCR). Analysis of liquid chromatography showed three new peaks, dammarenediol-II (DD), protopanaxadiol (PPD), and PPT, in leaves of transgenic tobacco. Transgenic tobacco (line 6) contained 2.8 μg/g dry weight (DW), 7.3 μg/g DW, and 11.6 μg/g DW of PPT, PPD, and DD in leaves, respectively. Production of PPT was achieved via cell suspension culture and was highly affected by auxin treatment. The content of PPT in cell suspension was increased 37.25-fold compared with that of leaves of the transgenic tobacco. Transgenic tobacco was not able to set seeds because of microspore degeneration in anthers. Transmission electron microscopy analysis revealed that cells of phloem tissue situated in the center of the anther showed an abnormally condensed nuclei and degenerated mitochondria. Conclusion: We successfully achieved the production of PPT in transgenic tobacco. The possible factors deriving male sterility in transgenic tobacco are discussed. Keywords: Male sterility, Metabolic engineering, Protopanaxatriol, Sapogenin, Transgenic tobacco